If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(6n+7)=-3+3n
We move all terms to the left:
-6(6n+7)-(-3+3n)=0
We add all the numbers together, and all the variables
-6(6n+7)-(3n-3)=0
We multiply parentheses
-36n-(3n-3)-42=0
We get rid of parentheses
-36n-3n+3-42=0
We add all the numbers together, and all the variables
-39n-39=0
We move all terms containing n to the left, all other terms to the right
-39n=39
n=39/-39
n=-1
| 19y-42=258-11y | | -3x-3(5x-1)=93= | | 1=30/2x | | -4x-5=8+6x | | 4x+7=7x-53 | | -32-7x=-7x-4(x+5) | | 3x–5=4+2x | | 1x/6+3=-18 | | 120x+0.70=60x+0.90 | | 10t-2=48 | | 3(8-x)-4=10 | | 6x+8=5x+22=180 | | 7y-8-5y=4 | | 285=225-u | | 3z-2z(z-8)=2+2z | | (4x+20)=(3x+35) | | 20-7m=6 | | V=a+3 | | 23=9-2w | | w=4w-87 | | 10-t/4=5 | | 6k+7=-7k+7(1+7k) | | 10x-30=84-8x | | 3^6=d | | (x-5)+(4x-10)+(5x-5)=180 | | 5(2x+3)=5x+15+5x | | 3x+6=21x-42 | | 5(2x+)=5x+15+5x | | C=5a-30 | | 3(-9-4n)-4=8n-9(n)+12 | | -5m+16=-60 | | 4n-(1+7n)=4n-36 |